2013
DOI: 10.5414/np300623
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of the Nissl substance as a manifestation of early damage to spinal cord motoneurons in amyotrophic lateral sclerosis

Abstract: In ALS, enlargement of the tigroid seems to be an early morphological feature - occuring earlier than central chromatolysis. Its presence may be connected with endoplasmic reticulum stress, disturbed axonal transport or functional compensation of the neuronal deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The Nissl substances, rough endoplasmic reticulum (RER) with rosettes of free ribosomes, are important for the protein synthesis 35 . The lost and dissolved of Nissl substances were observed in many neurodegeneration diseases, which were considered as importance factors for cognitive decline 36 , 37 . The quantitative analysis showed that the 2.856 GHz and 1.5 GHz microwave significantly reduced the contents of Nissl substances.…”
Section: Discussionmentioning
confidence: 99%
“…The Nissl substances, rough endoplasmic reticulum (RER) with rosettes of free ribosomes, are important for the protein synthesis 35 . The lost and dissolved of Nissl substances were observed in many neurodegeneration diseases, which were considered as importance factors for cognitive decline 36 , 37 . The quantitative analysis showed that the 2.856 GHz and 1.5 GHz microwave significantly reduced the contents of Nissl substances.…”
Section: Discussionmentioning
confidence: 99%
“…Nissl bodies are particularly rich in highly metabolically functional neurons. When neurons are damaged or overtired, the Nissl bodies can be reduced, disintegrated or can even disappear (Ajibade et al, 2009;Dziewulska et al, 2013). During the course of an injury or fatigue recovery, the Nissl bodies reappear, increase, and can reach a normal level.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not observed in this study at 6 months. Electron microscopy studies have shown extensive endoplasmic reticulum pathologies such as chromatolysis, membrane disruption, and displacement in motor neurons [ 81 , 82 ]. Evidence of chromatolysis was prevalent in motor neurons of vehicle-treated rats 6 months after avulsion while the surviving motor neurons of treated rats showed signs of recovery or preservation.…”
Section: Discussionmentioning
confidence: 99%